Efektivitas Capital Adequacy Ratio dan Nonperforming Loan Terhadap Profitabilitas Perbankan di Indonesia: Studi Manajemen Keuangan Perusahaan - Hariandy Hasbi; I Kadek Wira Dharama Prayana; Mekar Meilisa Amalia; Andi Hidayatul Fadlilah; Dede Hertina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The existence of banks as a subsystem in the economy of a country has an important role, even in the daily life of modern society most of them involve the services of the banking sector. The purpose of this study was to analyze the Capital Adequacy Ratio and Nonperforming Loan on banking profitability in Indonesia. The method used in this article is a qualitative method with literature study or Library Research. The aim is to analyze the comparison of existing theories with previous theories in the research literature. The literature used is literature from research results or reviews presented in national and international scientific articles related to financial management that discuss CAR and NPL that affect bank profitability. Based on the literature review conducted in this article, the following conclusions can be drawn: (1) Capital Adequacy Ratio (CAR) has a positive effect on banking profitability in Indonesia. (2) Nonperforming Loan (NPL) has a positive effect on banking profitability in Indonesia. Keywords: Capital Adequacy Ratio (CAR), Nonperforming Loan (NPL), Profitability